How Long a Motivation May Last? - Habibzadeh Nasim (Journal of Human Psychology, 2019)
Motivation is a kind of goal which ones could have over short or long terms in life. It could include both intrinsic and extrinsic types. Intrinsic motivations are composed of long term goals which associated with the internal individual‘s motivation whereas extrinsic motivations are empowered by external environments. Correspondingly, with considering the individual endurances, the type of hardships in different types of motivations is varied. In this between, the individual devotion in relation to their goal is determinate factors. Some people devoted their entire life to their goals, so how determinate you are?
Keywords: Motivation